FORMS OF LEGAL PROTECTION AGAINST INDONESIAN MSMES IN THE FIELD OF INTELLECTUAL PROPERTY RIGHTS - Edison Hatoguan Manurung; Ina Heliany (International Journal of Economy, Education and Entrepreneurship, 2021)
As a business actor, it is only natural that MSMEs need to pay attention to the intellectual Property of the products they produce. Even though as we know that the registration of Intellectual Property, be it Copyrights, Brands, Patents, Trade Secrets, Industrial Designs, and Integrated Circuit Layout Designs (DST), is a distinct advantage for MSME actors; there is still little interest in Indonesian MSMEs to register Intellectual Property. Unfortunately, because noting IPR can protect its business products without fear of being copied by other parties. Based on the description above, what will be discussed in this research is 1. How is the government's legal protection of Intellectual Property Rights in Indonesia? 2. What factors cause the reluctance of MSMEs to take advantage of the IPR system? 3. What is the potential for Intellectual Property Rights (IPR) that can be used for Indonesian Micro, Small, and Medium Enterprises (MSMEs)? The method used in this research is normative juridical research using secondary data in the form of intellectual property books and applicable laws and regulations. Based on the provisional assumption, it is known that the state of government legal protection for IPR in Indonesia is by enacting several rules relating to IPR, namely Law No. 30/2000 concerning Trade Secrets, Law no. 31/2000 regarding Industrial Design, Law no. 32/2000 concerning Layout Design of Integrated Circuits, Law no. 13/2016 on Patents, Law no. 20/2016 on Trademarks, Law no. 28/2014 on Copyright. The potential for Intellectual Property Rights (IPR) that can be used for Indonesian Micro, Small and Medium Enterprises (MSMEs) are Copyrights, Trademarks, Industrial Designs, and Trade Secrets and the factors that cause MSMEs reluctance to utilize the IPR system, namely, first, The registration procedure is long and complex. Secondly, the registration fee is expensive, and thirdly, it is related to the perception that law enforcement for IPR violations is feeble.